Determination of One and the Same Person as a Solution to Identity Disharmonies in Population Administration - Gunabila Bin’Arya Dwitatama; Mahdaniyal Hasanah Nuriyyatiningrum (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Identity inconsistencies in population administration are legal issues that impact legal certainty and the fulfillment of citizens' civil rights. Differences in the spelling of identities in official documents often hinder the implementation of legal actions, particularly in the administration of land rights. This study aims to analyze the legal considerations of judges in determining "the same person" and to assess the limits of the court's authority in voluntary population administration cases. The Research method used is normative legal Research, with a legislative, case, and conceptual approach, focusing on the Semarang District Court Decision Number 356/Pdt.P/2025/PN Smg. The results of the study show that the determination of "the same person" not only serves as a declaration of legal status but also clarifies the scope of court authority, emphasizing its role in ensuring consistent legal outcomes for population and land rights issues.